Ritual and Continuity Paradox. Between the Present and the Past - Introductory Theoretical Issues - Tak, Herman (INSTED: Interdisciplinary Studies in Education & Society, 1998)
The author makes a critical analysis of ritual in a structural attempt, as ?the world of time out of the time?. He considers two functions of ritual: building social solidarity and supporting antagonisms in society. He indicates the changes taking place in contents and forms of ritual, disappearance of its social understanding, which significantly influences the realisation of the function of ritual as a cultural identity transmitter.